A Nonflammable and Thermotolerant Separator Suppresses Polysulfide Dissolution for Safe and Long‐Cycle Lithium‐Sulfur Batteries - Lei, Tianyu; Chen, Wei; Hu, Yin; Lv, Weiqiang; Lv, Xiaoxue; Yan, Yichao; Huang, Jianwen; Jiao, Yu; Chu, Junwei; Yan, Chaoyi; Wu, Chunyang; Li, Qiang; et al. (Advanced energy materials, 2018)
Lithium‐sulfur (Li‐S) batteries are of considerable research interest for their application potentials in high‐density energy storage. However, the practical application of Li‐S batteries is severely plagued by polysulfide (PS) dissolution and serious safety concerns caused by flammable sulfur and polymer separators. Herein, a nonflammable multifunctional separator for efficient suppression of PS dissolution and high‐temperature performance of Li‐S batteries is reported. Polyacrylonitrile (PAN) and ammonium polyphosphate (APP) are electrospun into a multifunctional separator (PAN@APP) for stable and safe Li‐S batteries. Owing to the abundant amine groups and phosphate radical in APP, the PAN@APP separator has strong binding interactions with PS, which exerts strong charge repulsion to suppress the transport of negatively charged PS ions and free radicals. Furthermore, refractory APP ensures the stability of the battery at high temperatures. Using the PAN@APP separator, the Li‐S battery demonstrates a capacity retention of 83% over 800 cycles. This work provides a robust materials platform for stable and safe Li‐S batteries and points to a direction to close the current gap facing the commercialization of high‐energy next‐generation electrochemical conversion/storage devices. Owing to the abundant amine groups and phosphate radical, the reported novel separator has strong binding interactions with polysulfide (PS), which exerts strong charge repulsion to suppress the transport of negatively charged PS ions and free radicals. Furthermore, refractory ammonium polyphosphate ensures the stability of the battery at high temperatures.